Chromoblastomycosis caused by Rhinocladiella aquaspersa: first case report in Guatemala - Carlos Porras-López; María Guadalupe Frías-; Roberto Arenas; Erick Martínez-Herrera (Sociedade Brasileira de Dermatologia, 2019)
Abstract The authors report a case of 40-year-old male patient with a five-year history of chromoblastomycosis on his right leg. Diagnosis was performed by direct 40% KOH exam of skin scales, culture with micro- and macromorphologic analysis, and genotypic characterization (sequencing of a fragment of the ITS region and phylogenetic analysis) of the isolated fungus. Rhinocladiella aquaspersa was identified as the etiological agent. Initially, the treatment was with oral itraconazole 200 mg/day for one year. However, the presence of "sclerotic cells" with filaments ("Borelli spiders") resulted in a change of medical treatment: a higher dose of itraconazole (400 mg/day) and surgery, achieving clinical and mycological cure in one year. This is the first report of chromoblastomycosis caused by R. aquaspersa in Guatemala.